2005
DOI: 10.1143/jjap.44.l982
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Selective Growth of GaN on Maskless V-Grooved Sapphire Substrates by Metalorganic Chemical Vapor Deposition

Abstract: Selective growth of GaN on maskless V-grooved sapphire substrate is found by metalorganic chemical vapor deposition (MOCVD), where the V-grooved sapphire substrate is fabricated by chemical wet etching. GaN layers grow only on the (0001) mesas and no GaN growth occurs on the {110k} sidewalls of the V-grooves. The origin of the selective growth of GaN is unveiled and analyzed by energy dispersive X-ray (EDX) spectroscopy mapping. It is found that, Ga migration rates on the different facets are different clearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
(14 reference statements)
2
18
0
Order By: Relevance
“…An obvious broad shoulder was observed near the main peak for the conventional LED. It suggested that a better crystalline quality was achieved on CWE-PSS LEDs and was consistent with the well accepted concept that the growth on the pattern sapphire substrate exhibited a considerable improvement on internal quantum efficiency by reducing the threading dislocation density, no matter on dry etching or chemical wet etching patterned sapphire substrates [9]- [15]. Fig.…”
Section: Gan-based Leds Grown On Chemical Wet-etched Patterned Sasupporting
confidence: 83%
“…An obvious broad shoulder was observed near the main peak for the conventional LED. It suggested that a better crystalline quality was achieved on CWE-PSS LEDs and was consistent with the well accepted concept that the growth on the pattern sapphire substrate exhibited a considerable improvement on internal quantum efficiency by reducing the threading dislocation density, no matter on dry etching or chemical wet etching patterned sapphire substrates [9]- [15]. Fig.…”
Section: Gan-based Leds Grown On Chemical Wet-etched Patterned Sasupporting
confidence: 83%
“…No GaN layers are deposited on the sapphire sidewalls, and GaN growth occurs only on the mesas. Energy dispersive X-ray analysis (EDXA) was performed on GaN samples with different growth stages including low-temperature nucleation, hightemperature anneal, and high-temperature growth of GaN on patterned sapphire, it is confirmed that the selective growth is attributed to the different migration rates of Ga atoms on the sidewalls and mesas at high temperatures [11]. The structural characteristics of samples in Fig.…”
Section: Methodsmentioning
confidence: 78%
“…Therefore, although the mask may affect wing tilt in ''conventional'' LEO of GaN, it is not the root cause. Recently, we have developed a new means [11], in which V-grooved sapphire substrates are prepared by wet chemical etching. The absence of GaN deposited on the facets of the grooves avoids the propagation of TDs from the GaN layers on the sidewalls of the grooves, typically present in CE, and thus crystal quality can be improved further.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Five-centimeter (i.e., 2 inch) (0001) sapphire wafers with a 0.25-degree misorientation toward the h1100i direction are used, and a pattern of stripes along the h1120i sapphire direction is found to be suitable for our GaN CBE method. The detailed fabrication process is described below.…”
Section: Fabrication Of a Patterned Sapphire Substrate By Chemical Etmentioning
confidence: 99%
“…In this brief Research News article, we, at the Institute of Physics, the Chinese Academy of Sciences, will give an introduction to our recent achievements: the first is in GaN lateral epitaxial overgrowth (LEO) techniques to decrease dislocation densities, [4][5][6] the second involves an asymmetricaly coupled quantum well (QW) structure with coupled wide and narrow InGaN/GaN QWs to increase the luminescent efficiency, [7] and the third is the development of a single-chip phosphorfree white LED. [8] Finally, an outlook of future work is discussed.…”
Section: Introductionmentioning
confidence: 99%